High‐frequency resonance in HVDC and wind systems: Root causes and solutions - Jian Sun; Ignacio Vieto; Christoph Buchhagen (IET Renewable Power Generation, 2023)
Abstract This paper presents methods to model and solve high‐frequency resonance problems in HVDC and wind power systems. Control and digital PWM delays are identified as a common root cause for such resonances. A systematic method to include such delays in small‐signal sequence impedance models is presented. The developed models are fully validated and used to characterize the effects of delay on system stability. In addition to full models that can predict the associated impedance and negative damping behaviour accurately, simplified approximate models are also presented to gain insights. The method is applied to type‐III and type‐IV turbines as well as HVDC converters based on modular multilevel converters (MMC). In addition to resonance of MMC and wind turbines with overhead transmission lines, the paper also identifies several other modes of high‐frequency resonance, including resonance between wind turbines and MMC HVDC converters, among different wind turbines, and between MMC HVDC converters and cables. Different methods to damp high‐frequency resonances are also discussed and demonstrated.